2021
DOI: 10.1111/mec.15893
|View full text |Cite
|
Sign up to set email alerts
|

Use of waggle dance information in honey bees is linked to gene expression in the antennae, but not in the brain

Abstract: Exchanging information is essential in all animal societies. Communicating about resources, reproductive state, group membership, and threats are vital in ensuring the survival and success of the group. However, relying on social information is often not the only available option, for example to find a food source, but searching for a resource individually can often be the better

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 133 publications
(196 reference statements)
2
11
0
Order By: Relevance
“…However, in the context of our study, what is important to note is that the opportunity for social learning did not have the same effect on all bees-the negative relationship between performance in the two tasks shows that the ones who did better in one task did worse in the other, which shows that there is interindividual variability in the use of social information. This difference in performance could be related to the salience or sensitivity to a social cue and individual variation regarding it based on underlying neurophysiological mechanisms [27,42,43]. Given the higher cost for an individual to acquire information on its own, such variation could also be related to energetic differences among individuals since metabolic rate has been widely considered as a fundamental variable underlying slow-fast phenotypic differences [7,11], including those in honeybees [44].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the context of our study, what is important to note is that the opportunity for social learning did not have the same effect on all bees-the negative relationship between performance in the two tasks shows that the ones who did better in one task did worse in the other, which shows that there is interindividual variability in the use of social information. This difference in performance could be related to the salience or sensitivity to a social cue and individual variation regarding it based on underlying neurophysiological mechanisms [27,42,43]. Given the higher cost for an individual to acquire information on its own, such variation could also be related to energetic differences among individuals since metabolic rate has been widely considered as a fundamental variable underlying slow-fast phenotypic differences [7,11], including those in honeybees [44].…”
Section: Discussionmentioning
confidence: 99%
“…More functional approaches are needed to move beyond correlation and investigate whether a causal link exists between the expression levels of the genes that we identified and the performance of dance behaviour. For example, a recent study has revealed that gene expression associated with sensory perception rather than high cognitive functions is more important for bees following a dance when deciding whether to use personal information vs. social cues (the waggle dance) when engaging in the next foraging trip (Kennedy et al, 2021): it could be tested whether sensory perception has a role in the regulation of dance behaviour as well, by analysing gene expression in other brain parts such as the antennal or optic lobes that are clearly linked to the processing of sensory inputs. We are aware that other internal or external factors could contribute to define the patterns of gene expression in the honeybees that we analysed, as the brain is a complex organ that responds to a wide range of factors and stimuli that we could not control totally, such as bee age or number of dances performed, just to mention a few.…”
Section: Rfementioning
confidence: 99%
“…Despite this, we still do not have a complete picture of how the waggle dance is regulated at the brain level. Pioneering studies have started to reveal some of the key players at the levels of molecules (Barron et al, 2007;Kennedy et al, 2021;Linn et al, 2020), cell types (Kiya et al, 2007) and genetic pathways (Sen Sarma et al, 2009) associated with dance communication, but it is unclear what genes in the honeybee brain trigger the performance of dance behaviour once activated.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, by recording the behaviour and spatial position of the ants shortly before sampling, we would like to gain insights into whether and how gene expression in the brain or antenna parallels behavioural changes in the hosts. While many studies focus on transcriptomic changes in the central nervous system, i.e., the brain, which not only processes information from the sensory organs but also directly controls behaviour and thus largely reflects an individual's behavioural phenotype (Robinson et al, 2008), recent work suggests that also the peripheral nervous system, the antennae, play a major role in determining an individual's behavioural phenotype (Caminer et al, 2023; Kennedy et al, 2021). Thus, we decided to sequence both of these tissues to additionally unravel the molecular basis of behaviour.…”
Section: Introductionmentioning
confidence: 99%